Early Markers of Liver Fibrosis in Children with Beta-thalassaemia Major: A Cross-sectional Study - Himani Aggarwal; Monica Verma; Shuchi Bhalla; Dinkar Yadav; Kapil Bhalla; Abhishek Soni (Journal of Clinical and Diagnostic Research)
Introduction: Hepatic fibrosis secondary to iron overload in beta-thalassaemia is a known complicating factor. Liver biopsy is considered the gold standard; however, it is burdened with a multitude of risks, highlighting the need for ongoing studies to evaluate the risk of fibrosis using less invasive methods. Aim: To evaluate the diagnostic utility of non invasive liver parameters such as the Aspartate Aminotransferase to Platelet Ratio Index (APRI) and the Fibrosis-4 Index (FIB-4) in detecting liver fibrosis, as well as the potential of YKL-40 (tyrosine (Y), lysine (K), leucine (L)) as an early marker of liver dysfunction by correlating it with Transient Elastography (TE) in children with beta-thalassaemia major receiving regular transfusions. Materials and Methods: This descriptive, cross-sectional study was conducted in the Department of Paediatrics, along with the Department of Hepatology and Gastroenterology, at Pt. B.D. Sharma Postgraduate Institute of Medical Sciences (PGIMS), Rohtak, Haryana, India, between January 2020 and February 2022. The study consisted of 75 paediatric patients with beta-thalassaemia major. Early markers for liver fibrosis were evaluated using serum YKL-40 levels, APRI, and FIB-4 scores, which were then compared to fibrosis scores obtained from TE. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) software version 20.0. Results: The mean age of the patients was 10.71±2.54 {mean±Standard Deviation (SD)} years, with a median age of 11 years and an age range of 6 to 16 years. In terms of diagnostic performance, YKL-40 (pg/mL) emerged as the best parameter regarding both Area Under the Receiver Operating Characteristics (ROC) Curve (AUROC) and sensitivity, demonstrating its strong ability to detect liver fibrosis. At a cut-off of APRI ≥0.356, APRI performed best in terms of specificity (98%). The AUROC for APRI was 0.937 (95% CI: 0.84-1), indicating very strong predictive capability and statistical significance (p<0.001). YKL-40 (pg/mL) emerged as the most effective parameter for negative predictive value, with an AUROC of 0.971 (95% CI: 0.924-1) in predicting fibrosis. Overall, both YKL-40 and APRI showed the highest diagnostic accuracy, highlighting their complementary roles in assessing liver dysfunction. Conclusion: Regular transfusions in beta-thalassaemia major often lead to iron overload and liver fibrosis. Non invasive tools like APRI, FIB-4, and the biomarker YKL-40 show promise as alternatives to biopsy and elastography, enabling earlier detection and intervention.